NIRS for vicine and convicine content of faba bean seed allowed GWAS to prepare for marker-assisted adjustment of seed quality of German winter faba beans - Winda Puspitasari; Björn Allemann; Deepti Angra; Helen Appleyard; Wolfgang Ecke; Christian Möllers; Tanja Nolte; Randy W. Purves; Carsten Renner; Thomas Robertson-Shersby-Harvie; Rebecca Tacke; Alex Windhorst; et al. (Journal für Kulturpflanzen, 2022)
GWAS was applied to the antinutritive compounds vicine and convicine (V, C) in winter faba bean. V, C and V + C data for 189 inbred lines (five environments) were predicted by NIRS. These lines do not carry the strong “vc-“ allele (locus VC1). Lab data for 646 samples enabled our NIRS calibration, which performed well for V and V + C yet poor for C. Heritability was high (0.911; 0.868) for V and V + C and lower for C (0.737). From the 2542 mapped SNPs, 47 were significantly associated with V and one with V + C. Four SNPs mapped near to the VC1 locus and were significant for V. Seemingly, non-“vc-“ alleles at that locus contributed to V variation. Marker-assisted breeding with this germplasm can reduce the V + C content to about 0.44%, compared to the current lowest line with 0.55%. Further research will show inasmuch this can serve agronomy and breeding.